Development and evaluation of a synthetic Cu-Zn-reinforced biphasic calcium phosphate scaffold for periodontal bone repair - Novelia, Devina; Cahyadi, Theophani O.; Sidharta, Natasya MP.; Octavia, Mora; Situmorang, Evi UM.; Edbert , Daniel (Narra J, 2026)
Periodontal bone defects require bone grafting materials that provide structural stability, biocompatibility, and reliable biological performance. Synthetic alloplastic scaffolds composed of biphasic calcium phosphate, integrating hydroxyapatite (HAp) and β-tricalcium phosphate (β-TCP), offer a promising alternative to other graft materials. Polycaprolactone provides flexibility and support for pore formation, while copper (Cu) and zinc (Zn) ions contribute to their antimicrobial and osteogenic benefits. This study aimed to investigate the physicochemical, morphological, mechanical, and biological properties of a synthetic HAp40/β-TCP60 alloplastic scaffold reinforced with polycaprolactone and to compare them with those of a commercial xenograft. The scaffold was fabricated using a freeze-drying method with dimethylformamide, and characterization included Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) for chemical and crystalline confirmation, Archimedes principle for porosity, light microscopy, and scanning electron microscopy (SEM) for morphological assessment, compressive testing, blood adhesion, as well as water and blood absorption analysis. FTIR and XRD verified the successful incorporation of polycaprolactone and the formation of a well-ordered biphasic calcium phosphate structure. Light microscopy showed that the synthetic scaffold had smaller macropore dimensions (324±49 µm) than the control (1410±541 µm), while SEM demonstrated markedly higher microporosity (8.184±2.581 µm) compared to the control (0.287±0.091 µm). Water absorption was lower in the synthetic scaffold (174.7%) than in the control (1172.5%), whereas blood absorption was comparable (300% vs 316.6%). The synthesized scaffold also exhibited superior blood adhesion, as evidenced by the absence of turbidity after agitation. Mechanical testing revealed that the control had superior compressive and yield strengths (0.980 MPa and 0.537 MPa, respectively) compared to the synthesized scaffold (0.287 MPa and 0.126 MPa, respectively). In conclusion, the synthetic HAp40/β-TCP60 scaffold exhibited properties within optimal ranges, highlighting its potential as a promising synthetic alloplastic material for clinical bone regeneration.